Addition of Whole Wheat Flour During Injera Fermentation Degrades Phytic Acid and Triples Iron Absorption from Fortified Tef in Young Women. Issue 10 (17th August 2020) - Herter-Aeberli, Isabelle; Fischer, Maren M; Egli, Ines M; Zeder, Christophe; Zimmermann, Michael B; Hurrell, Richard F
ABSTRACT: Background: Iron deficiency is a major public health concern in Ethiopia, where the traditional diet is based on tef injera. Iron absorption from injera is low due to its high phytic acid (PA) content. Objectives: We investigated ways to increase iron absorption from FeSO4 -fortified tef injera in normal-weight healthy women (aged 21–29 y). Methods: Study A ( n = 22) investigated the influence on fractional iron absorption (FIA) from FeSO4 -fortified injera of 1 ) replacing 10% tef flour with whole wheat flour (a source of wheat phytase), or 2 ) adding an isolated phytase from Aspergillus niger . Study B ( n = 18) investigated the influence on FIA of replacing FeSO4 in tef injera with different amounts of NaFeEDTA. In both studies, the iron fortificants were labeled with stable isotopes and FIA was calculated from erythrocyte incorporation of stable iron isotopes 14 d after administration. Results: In study A, the median (IQR) FIA from the 100% tef injera meal was 1.5% (0.7–2.8%). This increased significantly ( P < 0.05) to 5.3% (2.4–7.1%) on addition of 10% whole wheat flour, and to 3.6% (1.6–6.2%) on addition of A. niger phytase. PA content of the 3 meals was 0.62, 0.20, and 0.02 g/meal, respectively. In study B, the median (IQR) FIA from the 100% tef injera meal was 3.3% (1.1–4.4%) and did not change significantly ( P > 0.05) on replacing 50% or 75% of FeSO4 with NaFeEDTA. Conclusions: FIA from tef injera by young women was very low. NaFeEDTA was ineffective at increasing iron absorption, presumably due to the relatively low EDTA:Fe molar ratios. Phytate degradation, however, greatly increased during tef fermentation on addition of native or isolated phytases. Replacing 10% tef with whole wheat flour during injera fermentation tripled FIA in young women and should be considered as a potential strategy to improve iron status in Ethiopia.